2016
DOI: 10.1111/acer.13252
|View full text |Cite
|
Sign up to set email alerts
|

Binge Ethanol Consumption Increases Inflammatory Pain Responses and Mechanical and Cold Sensitivity: Tigecycline Treatment Efficacy Shows Sex Differences

Abstract: BackgroundPhysicians have long reported that patients with chronic pain show higher tendencies for alcohol use disorder (AUD), and AUD patients appear to have higher pain sensitivities. The goal of this study was to test 2 hypotheses: (i) binge alcohol consumption increases inflammatory pain and mechanical and cold sensitivities; and (ii) tigecycline is an effective treatment for alcohol‐mediated‐increased pain behaviors and sensitivities. Both female and male mice were used to test the additional hypothesis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 46 publications
0
22
2
Order By: Relevance
“…There was no effect of tigecycline on blood alcohol elimination, which was expected as we had not previously detected a change in the pharmacokinetic elimination of alcohol with minocycline or tigecycline in C57BL/6J mice (Agrawal et al., ; Syapin et al., ). Interestingly, while we did see sex differences in the antidrinking and antinociceptive actions of tigecycline in our companion studies (Bergeson et al., ; Syapin et al., ), we saw no sex differences or interactions in its ability to reduce alcohol‐withdrawal‐related seizure activity. Given that sex differences are known in general seizures (van Luijtelaar et al., ), coupled with the long‐known important role of sex as a factor in alcohol actions, including for withdrawal effects (Wiren et al., ), this was surprising.…”
Section: Discussioncontrasting
confidence: 45%
“…There was no effect of tigecycline on blood alcohol elimination, which was expected as we had not previously detected a change in the pharmacokinetic elimination of alcohol with minocycline or tigecycline in C57BL/6J mice (Agrawal et al., ; Syapin et al., ). Interestingly, while we did see sex differences in the antidrinking and antinociceptive actions of tigecycline in our companion studies (Bergeson et al., ; Syapin et al., ), we saw no sex differences or interactions in its ability to reduce alcohol‐withdrawal‐related seizure activity. Given that sex differences are known in general seizures (van Luijtelaar et al., ), coupled with the long‐known important role of sex as a factor in alcohol actions, including for withdrawal effects (Wiren et al., ), this was surprising.…”
Section: Discussioncontrasting
confidence: 45%
“…Considering the strong microglial inhibition caused by minocycline (Garrido‐Mesa et al., ), tigecycline may share some of the actions and similarly have sexually distinct effects (Sorge et al., ). In fact, our companion paper’s results showed that tigecycline reduced neuroinflammatory pain in males, but not in females (Bergeson et al., ). Additionally, tetracyclines may affect a variety of nonmicrobial processes and it is possible some of the mechanisms show sex differences at higher doses, which lead to no further decrease in EtOH consumption in the female mice.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, in rodent models of AUD, females display increased alcohol consumption relative to males, while the converse is observed in humans (Becker and Koob, ). Therefore, the results of Bergeson and colleagues () are particularly interesting, given that in rodent models, females are reported to be less affected by pain from alcohol withdrawal severity (Becker and Koob, ). One possible explanation for the paradoxical pro‐nociception reported for females in Bergeson and colleagues () may include the differential effects of tigecycline on pain responses in male versus female mice, which could involve cell‐specific immune‐related responses.…”
Section: Tigecycline and Sex Differences In Pain Responsementioning
confidence: 99%
“…Therefore, the results of Bergeson and colleagues () are particularly interesting, given that in rodent models, females are reported to be less affected by pain from alcohol withdrawal severity (Becker and Koob, ). One possible explanation for the paradoxical pro‐nociception reported for females in Bergeson and colleagues () may include the differential effects of tigecycline on pain responses in male versus female mice, which could involve cell‐specific immune‐related responses. For example, sex‐dependent developmental expression of TLR in microglia (Lenz et al., ) in addition to differences in T‐cell activation in rodents has been reported (Sorge et al., ).…”
Section: Tigecycline and Sex Differences In Pain Responsementioning
confidence: 99%
See 1 more Smart Citation